An Approach to the Simultaneous Detection of Multiple Biomarkers for the Early Diagnosis of Liver Cancer Using Quantum Dot Nanoprobes. Issue 1 (March 2022) - Cheng, Ningtao; Fu, Jing
Abstract : Abstract: Biomarker-based early diagnosis of liver cancer is of high clinical value for reducing the mortality rate. However, it has been challenging to establish early detection methods with a single biomarker such as alpha-fetoprotein (AFP) because of limited diagnostic sensitivity and specificity. Therefore, developing multiplexed biomarker detection assays is crucially important for early diagnosis. Yet, simultaneous detection methods involving three or more biomarkers have been scarce. Here we suggest employing the serological biomarker panel of glypican-3 (GPC3), dickkopf-1 (DKK1), and AFP for liver cancer detection. We present a rapid simultaneous detection approach for the biomarker panel labeled with three fluorescent quantum dot nanoprobes (emission wavelengths at 565 nm, 605 nm, and 655 nm). As a proof-of-concept, simultaneous fluorescence detection of the biomarker panel was demonstrated using mixed reference samples containing human recombinant GPC3, DKK1, and AFP antigens. Our simultaneous detection approach conferred a linear range of 0.625-2.5 ngmL -1 for the entire biomarker panel, which merits further clinical validation for the simultaneous and accurate determination of the biomarker panel in human serum samples.